Socialization process in the context of spiritual development of the person - Pomytkin, E. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The essence of the socialization process by reference to the spiritual development of personality. Analyzed category of spirituality, motivation, and psychological mechanisms as components of a psychological model of the process of spiritual development of personality. The examples of non-constructive and constructive socialization, which involves the orientation of spiritual ideals, meanings and values.